Feasibility Study on Protecting the Reputation of Celebrities Under the Passing Off Doctrine - Ali Nazari; Abbas MirShekari (پژوهشنامه حقوق تطبیقی)
In the event that the identity signs of celebrities are used in advertising goods and services without their permission, legal systems have sought to provide solutions to protect these individuals. In the Common Law system, one traditional institution that has been utilized is the doctrine of passing off. According to this doctrine, no one has the right to introduce or offer their goods or services as those of another person, nor to use another's trademark in such a manner. While passing off in its traditional sense applies when a defendant presents their product as one produced by another, judicial proceedings have introduced a broader interpretation of this doctrine. Under this expanded concept, any situation in which consumers are deceived or misled regarding the origin of goods or their endorsement falls under the purview of passing off. Given this interpretation, the unauthorized use of a celebrity's identity signs may mislead consumers about the product's origin, quality, or endorsement. Consequently, celebrities can file lawsuits based on this doctrine to prevent the defendant's continued activities and seek compensation for any damages incurred. This article aims to examine the aforementioned doctrine and its evolution within Common Law, as well as to explore the approach of Iran's legal system in this context.